PENGARUH STRES SITUASI KERJA TERHADAP PSYCHOLOGICAL WELL-BEING PADA GURU HONORER MADRASAH IBTIDAIYAH DI KOTA TANGERANG - Raisata Makbulah, Fitri Lestari Issom (Perspektif Ilmu Pendidikan, 2017)
This study aims to determine the effect of stress on the job situation of psychological well-being. The population in this study is a honorary teachers in Islamic Elementary School in the City of Tangerang. This study uses a quantitative method with a sample of honorary teachers in Islamic Elementary School in the City of Tangerang amounted to 55 respondents. The sampling technique used was cluster sampling with 55 respondents. This study uses two scale that a scale of psychological well-being and stress scale were arranged by researcher based on the theories of stress advanced by Robbins & Judges (2013), Gibson, Ivancevich, Donelly & Konopaske (2012) and Newstrom & Davis (2002). Test hypothesis in this study using a regression analysis one predictors. Based on the analysis of data, this means that there is influence between stress on the job situation to the psychological well-being on a honorary teacher Islamic Elementary School (MI) in the city of Tangerang. The resulting negative influence, meaning that if the work situation of high stress levels, the levels of psychological well-being will be lower.